Optimization of crown and pinion using metal matrix composite - R.Charles Godwin (Elsevier, 2021)
In automobile industries, the differential plays an important role in transfer motion from engine to rear wheels. Vehicles are having single axle differential and double axle differentials, depending on the load-carrying capacity. The crown and pinion gears have been involved as a foremost theme of research interest, in the case of resolving major issues such as wear and lifespan. This study aims to generate a computational model of the crown and pinion gear using Finite element analysis. The individualities of a crown and pinion gear at dynamic conditions, load carrying capacity, and stresses are tried in this research. Low carbon steel, high carbon steel and high carbon steel with Silicon Carbide (at various proportions) are used as materials to verifying the suitability of crown pinion. Finally, the generated analytical results of individual material are compared and concluded that high carbon steel performs good in structurally in dynamic condition.